Laminated Intestinal Calculi – A Rare Complication of Crohn's Disease - Hugh J Freeman; Andrew Seal; David Li (Canadian Journal of Gastroenterology)
A 59-year-old male with a 36-year history of Crohn's disease and repeated resections for small intestinal strictures developed anemia and symptoms of an intermittent partial bowel obstruction. Barium studies showed recurrent small intestinal strictures as well as filling defects in a dilated loop proximal to a stenosed segment. Subsequent abdominal films and a computed tomographic study suggested laminated radiopaque calculi with peripheral calcification in the dilated small intestinal loop. Resection of the strictured segment confirmed the presence of intestinal enterolithiasis.